WAYS TO IMPROVE LISTENING AND SPEAKING SKILLS IN THE PROCESS OF COMMUNICATION THROUGH INNOVATIVE TECHNOLOGIES - Tulaboyeva, Gulorom (Журнал иностранных языков и лингвистики, 2023)
The teacher in the modern environment is not only a source of information and academic facts, he helps students understand the educational process, helps to find the information they need, whether they meet the requirements, and also understands how they use this information to answer the questions asked and make the decisions of the challenges. Teacher today is forced to regularly qualify in the field of innovative educational technologies.